Analysis of Euphemistic Language Style in the Novel Pukat by Tere Liye - Tara, Firman; Masni, Harbeng; Zahar, Erlina (International Journal of Multidisciplinary Sciences and Arts, 2024)
This research aims to describe and document the form, characteristics and meaning of euphemistic language styles in the novel Pukat by Tere Liye. This research is a type of qualitative descriptive research using a structural approach. The data in this research is the euphemistic language style in the novel Pukat by Tere Liye. Data collection techniques were carried out using library study and documentation techniques. The results of this research are that the euphemistic language style in the novel Pukat by Tere Liye is divided into 5 forms. These five forms can be broken down into euphemistic language styles, word forms, phrases, clauses, sentences and idioms. The use of euphemistic language styles is based on the most prominent form, namely the form of the word. Based on the research results, it can be concluded that euphemistic language styles based on word forms are more prominent in the novel Pukat by Tere Liye. Based on its characteristics, euphemistic language styles that have more subtle/polite diction are most often found. Meanwhile, based on its meaning, the euphemistic language style in the novel Pukat by Tere Liye has a more subtle meaning.